Socjoterapia wobec agresji rówieśniczej w szkole. Studium teoretyczno-empiryczne - Wilk, Maciej (My University, 2022)
Agresja rówieśnicza w polskich szkołach jest codziennością, mimo że jej poziom jest niższy niż w wielu innych krajach. Nie zmienia to faktu, że kłótnie, wyzwiska, złośliwości, popychanie, kopanie czy bójki są stałym doświadczeniem polskich uczniów. Już nie nowym, ale dynamicznie rozwijającym się problemem jest cyberbullying. Socjoterapia jako grupowa forma pracy z dziećmi i młodzieżą może stanowić formę przeciwdziałania temu zjawisku. Po pierwsze może być formą pracy z uczniami, których dotyka już problem agresji rówieśniczej w szkołach. Po drugie może stać się formą systematycznej pracy z dziećmi i młodzieżą w celu minimalizowania zagrożenia wystąpienia zjawiska agresji rówieśniczej w szkołach. Celem tej rozprawy było zweryfikowanie w oparciu o zdanie socjoterapeutów pracujących z dziećmi i młodzieżą i stykających się z problematyką agresji rówieśniczej w szkołach, w jaki sposób socjoterapia może być pomocna w pracy z tym problemem. Analiza wyników badań wskazała na dwa aspekty pracy z tym zjawiskiem. Pierwszy dotyczy opracowania szeroko realizowanej przez cały okres nauki różnego rodzaju socjoterapeutycznych zajęć, mających na celu wspieranie rozwoju dzieci i młodzieży, budowanie integracji ze środowiskiem szkolnym, realizowanie psychoedukacyjnych form zajęć. Drugi aspekt podkreślany przez badanych socjoterapeutów koncentruje się na pomocy uczniom, którzy mieli lub mają już kontakt z przejawami agresji rówieśniczej. Łączenie tych dwóch płaszczyzn socjoterapeutycznej pracy w opiniach badanych socjoterapeutów pozwalałoby minimalizować samo zjawisko agresji rówieśniczej w szkołach, jak również negatywne skutki jej występowania.

Peer aggression in Polish schools is an everyday occurrence, although its level is not as high as in other countries. It does not change the fact that manifestations of verbal aggression: maliciousness, nicknames, quarrels are rather commonplace for most Polish students. Physical aggressions such as shoving, fighting, kicking and destroying other people's property are less common. A new phenomenon of peer aggression is cyberbullying. Sociotherapy as a form of group work with children and youth can be treated as an answer to the phenomenon of peer aggression in schools, which can be realized through two basic tasks. The first task is the realization of corrective and remedial tasks in situations when schools, classes, and pupils already face aggressive and violent situations at school or in the wider school environment. The second task of sociotherapy is the preparation and realization of first level prevention, whose main goal is to develop procedures to minimize the occurrence of aggressive behavior, patterns of functioning of classes or school environment leading to peer violence, school bullying. The aim of this dissertation was to verify the above assumptions and statements with the experience of sociotherapists who struggle everyday with the difficulties of working with children and adolescents. The analysis of the results and data from the interviews with sociotherapists allows us to emphasize that sociotherapy can have a significant role in counteracting aggression and peer violence in Polish schools. The most important element of the process of counteracting peer aggression at schools should be systematic work with children and adolescents using psycho-educational trainings, workshops and many other kinds of sociotherapeutical techniques as a system of prevention. The second element of sociotherapeutic activities would be group workshops for children and youth who have already come into contact with the problem, either as victims of aggression, perpetrators, or observers. The systematic sociotherapeutical activities with children and youth, carried out from the very beginning of the educational process would be the most needed aim in the process of counteracting peer aggression at school.
Sociotherapy towards the Peer Aggression at School. Theoretical and Empirical Study
Wydział Studiów Edukacyjnych
Keywords: agresja; rówieśniczy; socjoterapia; zapobieganie; szkoła; aggression; peer; sociotherapy; prevention; school